Intestinal dysbiosis associated with non-nutritive sweeteners intake: an effect without a cause? - Marongiu, Luigi; Brzozowska, Ewa; Hetjens, Svetlana; Hoelzle, Ludwig E.; Venturelli, Sascha (Frontiers in Nutrition, 2025)
Non-nutritive sweeteners (NNS) are present in various commercial articles, from foodstuffs to oral hygiene products. Despite their alleged safety, mounting evidence indicates that NNS intake is associated with an alteration of intestinal bacterial populations (dysbiosis) in animals and humans. Since NNS are commercialized based on the assumption that they are not metabolized by human cells and negligible effect on bacterial, the insurgence of dysbiosis associated with NNS intake remains unexplained. The current review aims to assess the effect of selected NNS (acesulfame potassium, advantame, aspartame, neotame, saccharin, stevia, and sucralose) on the human intestinal microbiota. Findings from this review suggests that NNS intake is linked not only to alterations in human physiology but also to modifications of bacterial biochemistry, including the hindrance of quorum sensing pathways, in a species-specific manner. Moreover, there were suggestions that NNS could also affect the biology of phages, namely by binding to the active sites of proteins involved in the infection process and altering the induction rate of prophages. The studies gathered in the present review provide a framework for understanding how NNS might be connected to dysbiosis, both directly through alterations in bacterial biochemistry and indirectly through impaired phage activity.